Zur Synonymie einiger Scambus-Arten (Hymenoptera: Ichneumonidae). - Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1966)
The nomenclature of three frequent species of the genus Scambus (Sc. annulatus, Sc. planatus, Sc. brevicornis) is discussed. Five new synonyms are presented. Nomenclatural Acts ameformis Kéler, 1937 (Pimpla), syn. n. of Scambus (Scambus) brevicornis (Gravenhorst, 1829) longiventris Ratzeburg, 1848 (Pimpla), syn. n. of Scambus (Scambus) planatus Hartig, 1838 nucum Ratzeburg, 1844 (Pimpla), syn. n. of Scambus (Scambus) planatus Hartig, 1838 stramentaria Kriechbaumer, 1890 (Pimpla), syn. n. of Scambus (Scambus) planatus Hartig, 1838 trilobata Kéler, 1937 (Pimpla), syn. n. of Scambus (Scambus) annulatus (Kiss, 1924) planatus Hartig, 1838 (Scambus (Scambus)), Lectotype